Mediating Effect of Career Decision Self-Efficacy on the Relation of Perfectionism to Career Indecision (Jurnal Bimbingan Konseling, 2019)
The purpose of this research was to identify and analyze the prediction effects of perfectionism on the career decision self-efficacy and career indecision, career decision self-efficacy on the career indecision and the mediating effect of career decision self-efficacy on the relationship between perfectionism and career indecision. The sample involved 369 high school students selected using random cluster sampling. The research method used is a structural equation model. The results showed that self-oriented perfectionism positively predicted career decision self-efficacy while socially prescribed perfectionism negatively predicted career decision self-efficacy, as well as career decision self-efficacy to predict career indecision. Also, career decision self-efficacy has a mediating effect on the relationship of perfectionism with career indecisions. The implications of the findings of this study are discussed in the article.